Age-Related Changes in Aortic 3D Blood Flow Velocities and Wall Shear Stress: Implications for the Identification of Altered Hemodynamics in Patients with Aortic Valve Disease - van Ooij, Pim (J Magn Reson Imaging, 2015)
PURPOSE: To investigate age-related changes in peak systolic aortic 3D velocity and wall shear stress (WSS) in healthy controls and to investigate the importance of age-matching for 3D mapping of abnormal aortic hemodynamics in bicuspid aortic valve disease (BAV). METHODS: 4D flow MRI (fields strengths=1.5 – 3T; resolution=2.2–3.9x1.7–2.6x2.2–4.0mm(3); venc=150–250cm/s; TE/TR/FA=2.3–2.8ms/4.7–5.4ms/7–15°) was performed in 56 controls (age range: 19–78 years) and in two BAV patient groups each consisting of 10 subjects (group 1: 20–29 years, group 2: 52–57 years). Heat maps showing abnormal 3D velocity and WSS were created for the BAV patients by comparison with an age-matched and with an unmatched control group. The fraction of the aorta exposed to abnormal velocity/WSS was calculated relative to the total aortic volume/surface. RESULTS: Significant inverse relationships between age and healthy velocity/WSS were found (R(2)=0.32/0.39, P<0.001). For BAV group 1, abnormally elevated velocity/WSS was overestimated when compared with older controls (51–60 years) than when correctly age-matched (~25±14% vs. ~8±5%). For BAV group 2, abnormally decreased velocity/WSS was overestimated when compared with younger controls (21–30 years) than when correctly age-matched (~9±7% vs. 1±1%). CONCLUSION: Significant correlations exist between age and peak systolic velocity and WSS. Therefore, robust age-matching is important when creating abnormal 3D aortic velocity and WSS maps for patients with BAV.